Hubungan Penggunaan Strategi Pembelajaran Membaca Dengan Penguasaan Bahasa Arab di Sekolah Menengah Kebangsaan Agama - Nazimah, Ngah (2011)
The purpose of this study is to examine the relationship between the reading learning strategies (memory, cognitive, compensasy, metacognitive, affective and social) and students performance in Arabic language. It also examines the diffences in applying reading learning strategies based on the demographic factors. The sample of this study is 150 form three students from Sekolah Menengah Kebangsaan Agama in Perlis. The Strategy Inventory for Language Learning (SILL) V.7.0 (Oxford, 1990) which consists 34 questions is administered to 150 respondents. The result of this study indicates a positive and significant relationship between applying the reading learning strategies and Arabic performance. The Pearson Correlation results show a positive and significant correlation between reading learning strategies (memory, cognitive, compensasy, metacognitive, affective and social) and Arabic performance . This study also shows significant diffences in applying reading learning strategies based on gender and student academic performance. The Regression analysis indicates that cognitive strategy has a higher influence towards Arabic performance in Sekolah Menengah Kebangsaan Agama in Perlis rather than the memory, compensasy, metacognitive, affective and social strategies.